Community Empowerment through Cultivation and Consumption of Oyster Mushrooms as an Effort to Improve Nutritional Status in Kasomalang Kulon Tourism Village - Suryani Suryani; Khairul Ikhwan; Dwi Indah Kartika; Alfadhlani Alfadhlani; Fitratur Rahmah Agustina; Donal Ortega; Samnil Astuti Fitri; Sri Setiawati; Aprilya Roza Werdani; Fitria Mushollini (Journal of Community Service and Application of Science, 2026)
This community service aims to improve the nutritional status of the community through empowerment based on local potential, namely the cultivation and utilization of oyster mushrooms in Kalomalang Kulon Tourism Village. Oyster mushrooms are a food source rich in vegetable protein, fiber, vitamins, and minerals, so they have the potential to support the improvement of people's nutritional intake. The method of implementing activities includes nutritional counseling, oyster mushroom cultivation training, and demonstration of oyster mushroom-based food product processing. The approach used is participatory, involving community groups, especially housewives and farmer groups. The results of the activity showed an increase in public knowledge related to the nutritional value and benefits of oyster mushrooms, which was shown by the increase in pre-test scores of 43% and post-test scores of 96%.  In addition, the community is able to cultivate oyster mushrooms independently and develop various processed products, such as nuggets, stir-fried oyster mushrooms, and oyster mushroom chips. The mushroom maker has 11 employees, which consists of 3 parts. Nurseries and packing. This program also has an impact on increasing the consumption of nutritious food and opening up opportunities for local food-based household businesses. Thus, community empowerment through the cultivation and consumption of oyster mushrooms has proven to be effective as one of the strategies in improving the nutritional status and food independence of village communities. This activity is expected to continue and be replicated in other regions with similar potential.